Pengaruh Kompetensi Pedagogik Dan Profesional Guru Sekolah Menengah Kejuruan Pasca Sertfikasi Terhadap Komitmen Guru Melaksanakan Proses Pembelajaran - Ahyanuardi Ahyanuardi; Hambali Hambali; Krismadinata Krismadinata (Universitas Negeri Padang, 2018)
The purpose of this research is : (1) to determine if there is influence of pedagogic and professional competence of SMK teachers to teachers’ commitment after certification (2) to determine how much influence of pedagogic and professional competence of SMK teachers to teachers’ commitment after certification. This research is a quantative descriptive research. The data collecting instrument used was questionnaire and data analysis used was multiple regression technique. The result showed : (1) there is a significant effect from pedagogic and professional competence of SMK teachers to teachers’ commitment in study process after certification (2) the percentage of commitment, pedagogic and professional competence of certified teachers are still low on average.